Characteristics of global precipitable water in ENSO events revealed by COSMIC measurements. Issue 15 (15th August 2013) - Teng, Wen‐Hsin; Huang, Ching‐Yuang; Ho, Shu‐Peng; Kuo, Ying‐Hwa; Zhou, Xin‐Jia
Abstract : [1] Precipitable water (PW) retrievals from FORMOSAT‐3/Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) Global Positioning System (GPS) radio occultation (RO) measurements were analyzed and compared with those derived from Special Sensor Microwave/Imager (SSM/I) and Advanced Microwave Scanning Radiometer for Earth Observation System (AMSR‐E) during the El Niño‐Southern Oscillation (ENSO) events from 2007 to 2011. For the three ENSO events in 2007–2011, monthly mean binned COSMIC PW results are in a very high correlation (up to 0.98) with those of SSM/I and AMSR‐E over the ocean, generally with root‐mean‐square differences less than 4 mm. PW retrievals from the three satellites are also of similar latitudinal variations. However, the PW is slightly underestimated by GPS RO, in particular, in the tropical regions. This underestimate may be caused partially by the fact that not all RO measurements can reach the surface. Inter‐satellite PW anomaly comparisons for the winter months in the ENSO events, with respect to those during the neutral (non‐ENSO) months, show consistent ENSO signals with major PW anomaly near the central Pacific in the warm event and near the Indonesian region and east of Australia in the two cold events. However, the 2007/2008 La Niña is somewhat less correlated for COSMIC with AMSR‐E and SSM/I. For the stronger 2010/2011 La Niña, their PW anomalies are in higher correlations of about 0.8. Key Points: COSMIC monthly mean PW is in a very high correlation with SSM/I and AMSR-E PW. COSMIC, SSM/I and AMS-E PW anomaly comparisons show consistent ENSO signals.